2018
DOI: 10.3201/eid2406.172160
|View full text |Cite
|
Sign up to set email alerts
|

Bioclinical Test to Predict Nephropathia Epidemica Severity at Hospital Admission

Abstract: This test identifies patients at low, intermediate, and high risk for severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In severe cases, kidney failure can develop [10]. NE presents in three forms: mild, moderate, and severe [11,12]. Each form of the disease progression includes febrile, oliguric, and polyuric periods, followed by convalescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In severe cases, kidney failure can develop [10]. NE presents in three forms: mild, moderate, and severe [11,12]. Each form of the disease progression includes febrile, oliguric, and polyuric periods, followed by convalescence.…”
Section: Introductionmentioning
confidence: 99%
“…The severe form of NE is characterized by headache, vomiting, high fever (over 39.5 °C), and acute kidney injury. The most prominent clinical features of this form of NE are hemorrhagic symptoms including petechial, nasal, and internal bleeding [11][12][13]. The moderate form of the disease has similar symptoms but is more subtle.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly urinary IL-6 and urinary NGAL [12, 16] have been found to associate with the severity of AKI. The association of widely used C-reactive protein (CRP) with severe AKI in PUUV infection is less clear [17] [12]. We have previously found that the amount of proteinuria and hematuria in dipstick sample at the acute phase is associated with the severity of AKI in NE patients [18, 19].…”
Section: Introductionmentioning
confidence: 99%